Occupationally Induced Allergic Contact Dermatitis to Methylchloroisothiazolinone/Methylisothiazolinone Among Water Bottle Plant Workers. Issue 4 (July 2020) - Hollins, Lauren Claire; Hallock, Katherine; Disse, Max; Chu, Christopher; Szollas, Rosemary; Marks, James; Flamm, Alexandra
Abstract : Background: Methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) allergy has increased for the last decade, mostly not only because of high concentrations in cosmetics but also because of its use as a biocide in industrial settings. Objective: We report an outbreak of allergic contact dermatitis in 8 workers at a water bottling plant secondary to excess levels of MCI/MI in the cooling system, found to be at levels 5 times the manufacturer's recommendations. Methods: Of 15 workers in the plastic bottle manufacturing area, 8 developed dermatitis, and 4 were referred for patch testing using a 100-allergen panel applied and interpreted in the standardized method according to the North American Contact Dermatitis Group. Results: Four workers had a positive reaction to MCI/MI. An investigation at the plant revealed that the concentration of MCI/MI was 365 ppm. The manufacturer's recommended level was 48 ppm. The cooling system was subsequently flushed, and biocide levels decreased to recommended levels. Afterward, all the affected workers experienced clearance of their allergic contact dermatitis. Conclusions: Occupational sensitization to MCI/MI is on the rise, in this instance, because of excess levels in the cooling system. Our findings demonstrate the continued need for awareness of the allergenicity of this preservative in the occupational setting.